2013
DOI: 10.1016/j.red.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Creative destruction with on-the-job search

Abstract: This paper is about the labour market consequences of creative destruction with on-the-job search. We consider a matching model in an economy with embodied technological progress and show that its dynamics are profoundly affected by allowing on-the-job search. We obtain that the elasticity of unemployment with respect to growth shrinks from 1.63 to 0.13. Moreover, the underlying transmission channels change as the flow of obsolete jobs practically disappears and is replaced by a flow of job-to-job transitions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…What is more plausible is the idea that in recessions, there may be fewer opportunities for productivity growth through reallocation across sectors of the economy. We think recent search and matching models that include on-the-job search, such as Michau (2013) and Miyamoto and Takahashi (2011), could be helpful frameworks for further understanding the declines we document.…”
Section: Vb Job Matching and Employment Dynamicsmentioning
confidence: 98%
“…What is more plausible is the idea that in recessions, there may be fewer opportunities for productivity growth through reallocation across sectors of the economy. We think recent search and matching models that include on-the-job search, such as Michau (2013) and Miyamoto and Takahashi (2011), could be helpful frameworks for further understanding the declines we document.…”
Section: Vb Job Matching and Employment Dynamicsmentioning
confidence: 98%
“…7 I introduce three key novelties to these earlier works. First, as in Michau (2013), I allow for on-the-job search, motivated by the dual observations that job-to-job mobility is a critical component of life cycle career dynamics (Topel and Ward, 1992), and that it has declined substantially over the past decades. Second, I model technological innovation as endogenously determined by the selection process associated with entry and exit, building on a vast literature stretching back to Schumpeter (1942).…”
Section: 3mentioning
confidence: 99%
“…A more realistic framework should allow them to search on the job or train themselves to improve their relative productivity and avoid job destruction. Michaud (2007) has already shown that the predictive capacity of the Mortensen and Pissarides (1998) model is considerably improved when introducing on-the-job search 2 . An alternative approach proposed in our paper involves introducing human capital issues in the style of Ljunqvist and Sargent (2008) 3 .…”
Section: Introductionmentioning
confidence: 99%